Lived Experience of Business School Faculty in post COVID-19 New Normal (Journal of Business and Management Research, 2023)
Two years of COVID-19 pandemic was a unique experience for many of us. The impact of the pandemic in the academic sector was distinct. This study explored the impact of pandemic on business schools and business school teaching through the examination of the lived experience of business school faculty members. The Hermeneutic phenomenology was used to capture the lived experience of the faculties who were involved in online teaching during pandemic and are teaching in the post COVID-19 new normal at graduate and undergraduate level in different business schools in Nepal. The data were collected through in depth interviews. The analysis of the data revealed four themes: (1) Not ready for hybrid mode, (2) Possibility opened up by online experience, (3) Challenge to maintain academic standard, and (4) Measures to tackle behavioral change among students. The findings suggest that COVID-19 and the time after directed business education towards transformation. However, the Nepali business school and business school faculty members have a long ground to cover. The implication and limitation of the study have been indicated.